2021
DOI: 10.14202/vetworld.2021.709-720
|View full text |Cite
|
Sign up to set email alerts
|

Determination of residues of pesticides, anabolic steroids, antibiotics, and antibacterial compounds in meat products in Oman by liquid chromatography/mass spectrometry and enzyme-linked immunosorbent assay

Abstract: Background and Aim: Meat is a rich source of many nutrients and plays a vital role in human life however, meat safety is one of the top priorities of great concern for consumers today. More than 90% of human exposure to harmful materials is due to consumption of contaminated meat products. This study was designed to compare four valid analytical methods for the determination of organochlorine pesticides 2,4 D (2,4-dichlorophenoxyacetic acid), dichlorodiphenyldichloroethylene/ dichlorodiphenyltrichloroethane, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Humans are exposed to the 2,4-D herbicide, as are 27–28% of Canadian farmers working with corn, soybeans, and other grains [ 5 ]. Traces of pesticides, including 2,4-D, were found in meat products in markets in Oman [ 6 ]. This herbicide was found in high concentrations in aquatic environments in The Kibale National Park in Uganda, with water samples inducing thyroid and estrogen axis disrupting in vivo activities in Xenopus laevis , plus affecting development and behavior of this model organism [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Humans are exposed to the 2,4-D herbicide, as are 27–28% of Canadian farmers working with corn, soybeans, and other grains [ 5 ]. Traces of pesticides, including 2,4-D, were found in meat products in markets in Oman [ 6 ]. This herbicide was found in high concentrations in aquatic environments in The Kibale National Park in Uganda, with water samples inducing thyroid and estrogen axis disrupting in vivo activities in Xenopus laevis , plus affecting development and behavior of this model organism [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, imprudent use of tetracycline, including incorrect dosage and route of administration [ 23 , 24 , 25 ], may have contributed to the residue violations observed in this study. Previous studies have reported that failure to follow meat withdrawal periods and extra-label use of injectable tetracycline may be associated with antibiotic residues in the tissues of food animals [ 23 , 26 , 27 , 28 ]. Future studies are warranted to investigate practices of injectable antibiotic administration, including extra-label use, treatment documentation, and knowledge of antibiotic withdrawal periods in food animals with clinical illnesses, to elucidate the spectrum of these issues (after the implementation of changes in VFD regulations) at the farm level in the U.S.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the samples were transported to Haramaya University Laboratory, packed in an icebox and stored at a temperature of −18 to −20°C until they were further transported for analysis, drug administration and quality control authority laboratory. 24 Then, the samples were analyzed at the Ethiopian drug administration and quality control authority laboratory, Addis Ababa.…”
Section: Methodsmentioning
confidence: 99%